The Effect of Addition Probioticon Feed Towards Growth of Baung (Hemibagrus nemurus)in The Recirculation System - Sitanggang, Rosita; M Tang, Usman; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on April 07th-May 17st, 2019 in the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The aimof this study is to determine the effect of the best dose of probiotic addition of feed on the growth of baung. The container of this research used a 60x40x40 cm 3 aquarium with 20 aquariums with a stocking density of 15 prawns/aquarium. This study used a Completely Randomized Design (CRD) with one factor of five treatment levels and four replications. Each treatment was given the addition of probiotic as much as P1 (0 ml/kg), P2 (15 ml/kg), P3 (20 ml/kg), P4 (25 ml/kg), and P5 (30 ml/kg) feed. The results of the research showed that the best treatment was found in P3 (20 ml/kg) feed resulting in absolute weight growth of 5,16 g, specific growth rate of 2.64 g, growth absolute length of 3,27 cm,feed efficiency of 74,42%and survival rate of 91,66%.Keywords : Hemibagrusnemurus, Probiotic, Growth